Mary in the Apostolic Church in the Light of the Lucan Writings - Mielcarek, Krzysztof Wojciech (The Biblical Annals, 2020)
Lukan Mariology does not present a holistic picture of Jesus’ Mother, although no doubt it is fundamentally important for the narrative of Luke-Acts. The Infancy Narrative and the three further traditions disseminated in the main bulk of the Lukan work (Lk 8:21; 11:27-28; Acts 1:14) show that her person cannot be limited to her faith or motherhood only. The author of the third Gospel composed a careful set of scenes in order to share with his readers much fuller picture of Mary. Being a Mother of the Lord, she is also a disciple following God’s will and the teaching of her Son. In this study the author is looking for some fresh insights from the text applying methodology presented recently by C. Bennema and other scholars interested in the Gospels’ characters and their characterisation.